"Like" Sebagai Berhala Digital: Telaah Teologis Atas Penyembahan Diri Dalam Terang Ensiklik Caritas In Veritate - Kanaf, Gregorio; Tuga, Romana; Langga, Marianus P.; Siba, Reinildis; Runesi, Monika; Aba Ola, Charolus; Taolin, Hironimus (Pastoralia Jurnal Penelitian Dosen, 2025)
The phenomenon of the “like” on social media has shifted from a mere expression of appreciation to a powerful symbol of social validation. In today’s digital culture, “likes” often become a benchmark for self-worth and recognition, leading to a hidden form of self-worship. This study aims to examine the “like” as a digital idol in light of the theological teachings in the Caritas in Veritate encyclical. Using a qualitative method with theological and psychosocial approaches, this research analyzes how dependence on digital validation affects personal identity, social relationships, and spiritual life. The findings show that the “like” culture produces psychological issues such as anxiety, depression, and digital narcissism, and also contributes to the erosion of social and moral values. Self-worship in the digital realm undermines human relationships and weakens one’s spiritual calling as the image of God. Within the framework of Caritas in Veritate, it is revealed that true human development can only occur through truth and love, not through superficial digital recognition. The study concludes that critical reflection, ethical digital education, and the restoration of authentic relationships with God, self, and others are needed to transform the digital culture into a medium of love, rather than a platform for self-idolatry.